Advances in accounting behavioral research. vol. 26 - Karim, Khondkar E. (Advances in accounting behavioral research, 2023)
Focusing on research that examines both individual and organizational behavior relative to accounting, Advances in Accounting Behavioral Research provides an in-depth analysis and exchange of peer-reviewed knowledge across all areas of accounting behavioral research and the development, discussion, and expansion of theories from psychology, sociology, and related disciplines. From the effects of organizational commitment, the impact of stressors on performance, and responses to narcissism to the effects of auditor familiarity and the examination of personality traits, chapters in Volume 26 compile innovative and new explorations into the behavioral aspects of accounting and auditing. Working on both the individual and organizational level, this collection is essential reading for accounting students and educators, providing a unique, interdisciplinary forum with valuable insights on practice for those working in the field to better understand accounting domains.